Evaluasi Penerapan dan Implementasi Audit Internal Berdasar ISO 45001 di PT. A - Ricky Eriady; Jani Rahardjo (Jurnal Titra, 2023)
PT. A is a company engaged in the industrial gas sector which will later be sent to all companies in Indonesia because this company itself is the largest gas production and distributor company in Indonesia. This is proven because this company itself has spread throughout Indonesia such as Java, Kalimantan, Sumatra, and Sulawesi and of course, it has also dominated the market because this company has relations spread throughout Indonesia. Then at PT. A has also implemented ISO 45001: 2018 for comfort and safety when in the company's work environment. But in fact, when the external audit was conducted, there were still some findings obtained by external auditors. In addition, findings were also obtained because employees still found it difficult to understand and understand the importance of standard Occupational Safety and Health regulations that should be applied on the company's work floor. The purpose of ISO 45001 is as a coordinator, to publish, and promote the application and use of international work standards in a company, especially in the K3 section with the final result being a minimum number of work accidents or incidents in the work environment of the company concerned.